Small bowel segment with Meckel’s diverticulum volvulus related to short mesodiverticular band: a case report - Michał Zieliński; Patryk Kaczor; Grzegorz Jarczyk; Marek Jackowski (Journal of Medical Case Reports, 2023)
Abstract Background Meckel’s diverticulum is a remnant of the omphalomesenteric duct and occurs in only about 2% of people. Mesodiverticular band is the congenital remnant of the vitelline artery and is an even less often occurring phenomenon. Presented case We present the case of a 56-year-old Caucasian male who was admitted to the emergency department with a very intense, sudden abdominal pain, without past abdominal surgery history. Contrast enhanced computed tomography showed a possibly ischemic closed loop of the small intestine. Urgent laparotomy was performed, during which bloody content in the peritoneal cavity and torsed loop of the small intestine with Meckel’s diverticulum were found. The bowel loop and Meckel’s diverticulum were ischemic. At the tip of Meckel’s diverticulum there was a broken fibrous band extending to mesentery with pulsating artery. We did segmental resection of small intestine including Meckel’s diverticulum and primary end-to-end anastomosis. The patient had an unremarkable postoperative hospital stay and was discharged home after 5 days. Conclusion In our case, we describe a patient with the volvulus of a segment of small bowel and Meckel’s diverticulum, which eventually led to small bowel obstruction and ischemia. It was a very rare case that required urgent surgical treatment.